28 Do not attempt resuscitation: university of aberdeen student perspectives. Issue 3 (1st September 2017) - Koshias, Andreas; Gray, Emma; Currie, Graeme; Cleland, Jennifer
Abstract : Introduction: Do Not Attempt Resuscitation Orders(DNAR) and their contemporary counterparts are cornerstones of End of Life care and as such, of importance within medical education. Previous research indicates the need for a better understanding of patient and physicians perceptions of DNAR topics. Aims and methods: The objective of the study was to explore medical students(MS) and non-medical students perspectives on DNAR discussions(DNARD), and explore any differences. This was a cross-sectional questionnaire study. MS and Education students(ES) were asked how they felt regarding DNARD taking place in 5 scenarios, a number of questions regarding previous experience, knowledge of DNARD, future preferences, and basic demographics. Results: The number of valid respondents was 601 (375[MS], 226[ES]) representing a response rate of over 70%. There were statistically significant differences between MS and ES in the presented clinical scenarios and future preferences. Ranking of clinical scenarios, highest agreement to lowest, for DNARD to take place were: before surgery, when critically ill, at a GP appointment, on admission to hospital, at an outpatient appointment. Statistically significant demographic differences were also found: 93% of MS having heard of DNAR previously as compared to 59% of ES. Both groups held the view that a DNARD would be beneficial for them in the future but that they should have the final decision regarding DNAR. Conclusion: MS and ES were found to hold differing views regarding DNARD in scenario preferences and personal future preferences. However, the majority of both groups felt that DNARD would be beneficial to them in the future. References: . Mary Catherine Beach, R Sean Morrison. The Effect of Do-Not-Resuscitate Orders on Physician Decision-Making. Ethics, public policy, and medical economics 2002;50:2057–206. . Cathy Charles, Tim Whelan, Amiram Gafni. What do we mean by partnership in making decisions about treatment?BMJ1999;319:780. . James Downar, Tracy Luk, Robert W Sibbald, Tatiana Santini, Joseph Mikhael, Hershl Berman, Laura. Why Do Patients Agree to a "Do Not Resuscitate" or "Full Code" Order? Perspectives of Medical Inpatients. Journal of internal medicine2011;26(6):582–587. . Thomas H. Gallagher, Steven Z. Pantilat, Bernard Lo & Maxine A. Papadakis (1999) Teaching Medical Students to Discuss Advance Directives: A Standardised Patient Curriculum, Teaching and Learning in Medicine, 11:3, 142–147, DOI: 10.1207/S15328015TL110304 . Paul Garrud. (2011). Who applies and who gets admitted to UK graduate entry medicine? - an analysis of UK admission statistics. BMC Medical Education. 11:71. . General Medical Council. (2013). Chapter1: The changing shape of the profession and medical education. In: The state of medical education and practice in the UK report: 2013 . General Medical Council. 32. . GMC, 2010. End of life treatment and care: Good practice in decision-making. Specifically paragraphs 11, 132 and 134. Can be accessed at: http://www.gmcuk.org/guidance/ethical_guidance/end_of_life_care.asp . Todd E. Gorman, MD, FRCP(C), Ste'phane P. Ahern, MD, FRCP(C), Jeffrey Wiseman, MD, FRCP(C), MA, and Yoanna Skrobik, MD, FRCP(C). (2005). Residents' End-of-Life Decision Making with Adult Hospitalised Patients: A Review of the Literature. Academic Medicine. 80 (7), 622–633. . Gorton, A.J., Jayanthi, N.V.G., Lepping, P., Scriven, M.W., 2008. Patients' attitudes towards "do not attempt resuscitation" status. J Med Ethics . Vol 34; 624–626. . W. Hafferty, Joseph F. O'Donnell (2015). The Hidden Curriculum in Health Professional Education . United States of America: Dartmouth College Press. 5. . Karen Hancock, Josephine M Clayton, Sharon M Parker, Sharon Wal der, Phyllis N Butow, Sue Carrick, David Currow, Davina Ghersi, Paul Glare, Rebecca Hagerty, Martin HN Tattersall . (2007). Truth-telling in discussing prognosis in advanced life-limiting illnesses: a systematic review. Palliative Medicine . 21, 507–517. . Jan C. Hofmann, Neil S. Wenger, Roger B. Davis, Joan Teno, Alfred F. Connors, Norman Desbiens, Joanne Lynn, Russell S. Phillips. (1997). Patient Preferences for Communication with Physicians about End-of-Life Decisions . Annals of Internal Medicine . 1 July 1997. . NHS Scotland. (2016). NHSScotland. Available: http://www.gov.scot/Topics/Health/About/NHS-Scotland. Last accessed 25th Nov 2016. . NRS: National Records of Scotland. (2013). Religion, Scotland, 2001 and 2011. Available: http://www.scotlandscensus.gov.uk/documents/censusresults/release2a/rel2asbtable7.pdf. Last accessed 25th Nov 2016 . ONS: Office for National Statistics. (2011). Full story: What does the Census tell us about religion in 2011?. Available: http://www.ons.gov.uk/peoplepopulationandcommunity/culturalidentity/religion/articles/fullstorywhatdoesthecensustellusaboutreligionin2011/2013-05-16. Last accessed 25th Nov 2016. . Stephen R. Porter and Michael E. Whitcomb. (2005). NON-RESPONSE IN STUDENT SURVEYS: The Role of Demographics, Engagement and Personality. Research in Higher Education . 46 (2). . Amy Sanderson, David Zurakowski, Joanne Wolfe. (2013). Clinician Perspectives Regarding the Do-Not-Resuscitate Order. JAMA paediatrics . 167 (10), 954–958. . Scottish Government, 2010. Do Not Attempt Cardiopulmonary Resuscitation (DNACPR): Integrated Adult Policy. Reviewed 2015. Can be accessed at: http://www.gov.scot/Topics/Health/Quality-sImprovement-Performance/peolc/DNACPR . Clive Seale. (2010). The role of doctors' religious faith and ethnicity in taking ethically controversial decisions during end-of-life care. Journal of Medical Ethics . doi:10.1136/jme.2010.036194. . C O Sham, Y W Cheng, K W Ho, P H Lai, L W Lo, H L Wan, C Y Wong, Y N Yeung, S H Yuen, A Y C Wong. (2007). Do-not-resuscitate decision: the attitudes of medical and non medical students. Clinical Ethics . 33 (5), 261–265. . UKMCRG: UK Medical Careers Research Group (2001). 1999 cohort of UK Medical Graduates: Report of First Survey . Oxford: Institute of Health Sciences, University of Oxford. 14. . Jacqueline K. Yuen, M. Carrington Reid, and Michael D. Fetters. (2011). Hospital Do-Not-Resuscitate Orders: Why They Have Failed and How to Fix Them. Journal of General Internal Medicine . 26 (7), 791–797. . Rocksheng Zhong, Joshua Knobe, PhD, Neal Feigenson, JD, and Mark R. Mercurio, MD, MA. (2011). Age and Disability Biases in Paediatric Resuscitation Among Future Physicians. Clinical Paediatrics ., 1–4.